Selective Hypoxia‐Cytotoxin 7‐Fluoro‐2‐Aminophenazine 5, 10‐Dioxide: Toward "Candidate‐to‐Drug" Stage in the Drug‐Development Pipeline. Issue 32 (27th August 2019) - Dávila, Belén; Sánchez, Carina; Fernández, Marcelo; Cerecetto, Hugo; Lecot, Nicole; Cabral, Pablo; Glisoni, Romina; González, Mercedes
Abstract: 7‐Fluoro‐2‐aminophenazine 5, 10‐dioxide, 1, has displayed in vitro bioreductive selective cytotoxicity, which could acts towards tumors containing hypoxic regions. In this work, we describe some preclinical studies of compound1 confirming its in vivo antitumor activity. The synthesis of compound1 was scaled up to 3 g improving the micro‐scale yield. Some drug‐like properties for compound1 were theoretically‐predicted and others, i. e. aqueous‐solubility and toxicity ‐mutagenicity, in vivo chromosomal‐aberrations and ip acute LD50 ‐, were experimentally confirmed. Antitumoral activity was studied in mice bearing hypoxic 4T1‐breast‐tumor by assessing evolution of the tumor‐sizes, animal‐survival and bio‐chemical/hematological. Compound1 in vivo efficacy, with the absence of systemic toxicity, was confirmed.. Results highlight the potential of 7‐fluoro‐2‐aminophenazine 5, 10‐dioxide as promissory therapeutic agent for solid tumors. Abstract : Some preclinical studies of 7‐fluoro‐2‐aminophenazine 5, 10‐dioxide are described. In vivo evaluation demonstrates that this compound is an excellent anti‐tumoral agent in a model of breast cancer.